Relationship in Organizational Culture, Management Control System and Employee Performance in Perspective Model - Gun Gunawan Rachman; Nur Izatul Makiyah; Muhamad Iqbal Adrian (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2022)
Organizational culture plays a role in shaping the character and behavior of employees, while management control systems play a role in controlling employees so that they continue to do work by the provisions. The purpose of this study is to determine the effect of organizational culture and management control systems on employee performance. The research was conducted at PT. Sami Aji Tekstil by collecting data through a questionnaire filled out by 33 respondents. The data collected is primary data and the method used is a descriptive verification method with a quantitative approach. In this study, the statistical test tool used was Structural Equation Modeling Partial Least Square (SEM-PLS). The results of this study are expected to be a solution to solving problems with the performance of employees at PT. Sami Aji Tekstil. The results of this study prove that organizational culture affects employee performance and that management control system affects employee performance.